Incidence of Rh alloimmunisation and its effects on pregnancy outcome in a tertiary care hospital - Sharma, Shuchi; Das, Jayita; Sharma, Reena (International Journal of Research in Medical Sciences, 2025)
Background: Red cell alloimmunization results from transplacental passage of maternal antibodies that destroy fetal red cells. The aim of the study is to determine incidence, maternal and perinatal outcome in Rh negative pregnancy. Methods: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology, Shri Lal Bahadur Shastri Medical College, Mandi, Himachal Pradesh for period of one year from 01 January 2024 to 31 December 2024. All the pregnant women admitted in labour ward with Rh negative pregnancy were included in the study. Results: The incidence of Rh negative pregnancy was 6.1% in one-year study period. Most common age group was 26-30 years comprising 42.8% cases. Majority of the patients were multipara (53.57%). Only 1.78% Rh negative pregnant women had positive indirect Coombs test. One patient was delivered at 34 weeks of gestation, 3 (1.33%) at 36 weeks and 220 (98.21%) at term (37-40) weeks of gestation. About 10.71% neonates had neonatal jaundice, 87.05% neonates had uneventful neonatal outcome. Conclusions: Early detection, timely intervention and motivation of the Rh negative patients can prevent maternal, fetal and neonatal complications.